Discrete Molecular Copper(II) Complex for Efficient Piezoelectric Energy Harvesting Above Room‐Temperature. Issue 9 (19th January 2023) - Haldar, Rajashi; Kumar, Ajay; Mallick, Binit; Ganguly, Swaroop; Mandal, Dipankar; Shanmugam, Maheswaran
Abstract: Developing robust, wearable, and biocompatible energy harvesting devices with bulk oxides (ceramics and perovskites) is extremely hard to achieve due to their zero mechanical flexibility, heavy metal toxicity, and tunability of properties. Alternatively, discrete inorganic complexes can be an excellent choice to overcome the above‐stated issues, thanks to appropriate molecular engineering. Herein, we report an above‐room‐temperature ferroelectric discrete molecular complex [Cu(L‐phe)(bpy)(H2 O)]PF6 ⋅H2 O (1 ) which is suitable for piezoelectric energy harvesting due to its large values of piezoelectric co‐efficient ( d 33 =10 pm V −1 ) and spontaneous polarization ( P s =1.3 μC cm −2 ). Among the devices prepared with the composite films of polyvinyl alcohol (PVA) and various weight % composition of 1, the 10 Wt % composite shows the highest output voltage of 8 V, a power density of 0.85 μW cm −2, and output current of 5 μA, which is highest for any discrete inorganic complex reported to date. Abstract : Herein, the discrete molecular ferroelectric complex [Cu (L‐phe) (bpy) (H2 O)]PF6 ⋅H2 O (1 ) ( T c =350 K) with a large piezoelectric co‐efficient ( d 33 =10 pm V −1 ), is exploited for piezoelectric energy harvesting. Among the devices prepared with the composite films of polyvinyl alcohol (PVA) and various weight % composition of 1, the 10 wt % composite shows an output current of 5 μA is which is the highest for any discrete inorganic complex reported so far.